The Mechanism of Aureusidin in Suppressing Inflammatory Response in Acute Liver Injury by Regulating MD2 - Yang, Yi; Han, Chenyang; Sheng, Yongjia; Wang, Jin; Zhou, Xiaohong; Li, Wenyan; Guo, Li; Ruan, Shuiliang (Frontiers in Pharmacology, 2021)
Objective:In this study, we mainly explored the mechanism and target of the anti-inflammatory effects of Aur in acute liver injury. Methods:Lipopolysaccharide (LPS) was used to induce inflammatory injury in Kupffer cells (KCs) in vitro. After Aur treatment with gradient concentration, flow cytometry, PI staining and Hoechst 33342 staining were used to detect the apoptotic level of KCs, and enzyme-linked immunosorbent assay (ELISA) was used to detect the expression levels of inflammatory factors, including IL-1β, IL-18, and TNF-α, Western blot was used to detect the expression of TLR4, MD2, MyD88 and p-P65. Aur was labeled with Biotin, followed by Pull-down assay to detect its binding with MD2, Moreover, D-GalN/LPS was used to induce acute liver injury in mice in vitro, followed by Aur treatment by gavage. H&E staining was used to detect the pathological changes of liver tissue, IF assay was used to detect the expression of MD2,Western blot was used to detect the expression of relevatn proteins. Results: Aur pretreatment could significantly inhibit LPS-induced KC injury, down-regulate apoptotic level, inhibit the expression of inflammatory factors, decreasae the level of MDA and down-regulate the expression of MD2 in cells. Aur could inhibit the activation level of TLR4/MD2-NF-κB in a dose-dependent pattern, with superior effect of high-dose Aur than low-dose Aur. In the case of MD2 deletion, the effects of Aur were suppressed. Additionally, pull-down and co-immunoprecipitation assays show that Aur can bind with MD2 protein to inhibit the activation of TLR4/MD2-NF-κB. Results of mice experiments also showed that Aur could relieve liver injury, decrease the levels of ALT and AST, and simultaneously down-regulate the levels of inflammatory factors in tissues and peripheral blood. Conclusion：we found that Aur exerted an anti-inflammatory effect by directly targeting MD2 protein, further inhibiting the expression of TLR4/MD2-NF-κB, thereby relieving acute liver injury. Therefore, Aur might be a potential inhibitor for MD2.